Innovative Online Learning Based on 3CM (Cool-Critical-Creative-Meaningful) Learning to Increase Creativity and Good Character of Elementary School Students During the Covid-19 Pandemic - Wahyudi Wahyudi; Kristina Roseven Nababan; Tri Nova Hasti Yunianta; Erlina Prihatnani; Dani Kusuma (Universitas Negeri Semarang, 2021)
Being creative and having good character is the goal of education in Indonesia. The COVID-19 pandemic has become a challenge in achieving this goal. Since the learning process is carried out online. Teachers have difficulty in planning and implementing the lesson. It is because not all teachers have ability to use technology appropriately. Thus, the learning process is not as expected. This causes boredom in the learning process. Therefore, an appropriate online learning design is needed. In this case, the online learning that provides opportunities for students to develop critical, creative, meaningful thinking skills in fun and challenging ways. One of them is online learning design based on 3CM (Cool-Critical-Creative-Meaningful) learning. The research design used in the present research is descriptive qualitative and RnD (ASSURE model) with the output of the initial data analysis related to the perceptions of school principals, teachers, students and parents about online learning. Questionnaires, online interviews and online FGDs are applied to obtain the qualitative data. Data related to the development of learning activities can be seen from the design development process with the ASSURE model. The results obtained are 89.7% of the 271 teachers that use WhatsApp in the learning process. This causes boredom in learning process so that 72.12% of 271 teachers want to go back to school. The scores result of development of online learning design based on 3CM learning from the aspect of easy access to learning is 4.48 (very good), the content aspect, media and teaching materials is 4.57 (very good) from the assessment of 45 elementary school teachers. The score of student responses to the aspect of easy access to learning is 4.72 (very good), the score of the aspect of content (content), media and teaching materials is 4.72 (very good). To foster creativity and good character, online learning activities are carried out in 4 activities, namely 1) time to play and try challenges (cool), 2) time to criticize (critical), 3) time to be creative (creative), 4) time to reflect and find the meaning (meaningful).